Overcoming Barriers in Improving Literacy and Numeracy at Bulusari 1 State Elementary School, Pasuruan Regency. - Ria Wulandari; Noly Shofiyah; Machful Indra Kurniawan; Ainun Jariah; Rahmawati Antinie (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article presents a community service activity aimed at addressing barriers to improving students' literacy and numeracy at SD Negeri Bulusari 1 Kec. Gempol, Kab. Pasuruan. The primary challenge faced by teachers was their limited knowledge in literacy and numeracy. To tackle this issue, a solution was implemented through literacy and numeracy material socialization. The study reveals that this socialization initiative significantly enhanced teachers' understanding of literacy and numeracy concepts and their ability to design engaging literacy and numeracy activities. The results highlight the potential of material socialization as a practical and effective strategy to empower educators and positively impact students' learning outcomes. Highlights: The study focuses on a community service activity that addresses the challenges of enhancing literacy and numeracy among students, particularly at SD Negeri Bulusari 1 Kec. Gempol, Kab. Pasuruan. A key aspect of the solution is the implementation of literacy and numeracy material socialization, which significantly improves educators' understanding of these subjects and their ability to design effective activities. The research highlights the potential impact of material socialization as a practical strategy to empower educators and positively influence students' learning outcomes. Keywords: Community service, Literacy and numeracy, Material socialization, Educators, Students